Mathematical Model of the Carbon Monoxide Conversion in Porous Catalyst - Ved, O. P.; Tolchinsky, Yu.; Kapustenko, P. O. (The Italian Association of Chemical Engineering, 2011)
This article discusses the mathematical model of heat-build-up and component change in the multi-component gaseous mixture. The components take part in chemical reaction on a catalyst’s solid surface. The mathematical model describes pre-oxidation reaction of carbon monoxide to carbon dioxide. Practical situation, accounted by the studied model is that CO afterburning to C0₂ takes place in automobile engine’s exhaust gases for atmospheric condition improvement.